Camelot ([Burbank, Calif.] Warner Home Video, 1967)
A musical version of King Arthur and his court.
VHS.
From the play by Alan Jay Lerner based on the book, The Once and Future King, by T.H. White.
Film editor, Folmar Blangsted, music by Frederick Loewe.
Richard Harris, Vanessa Redgrave, David Hemmings, Franco Nero, Leionel Jeffries.
Keywords: Feature films; Arthurian romances; Musical films